2013
DOI: 10.1111/jmft.12017
|View full text |Cite
|
Sign up to set email alerts
|

Military‐Related Posttraumatic Stress Disorder and Intimate Relationship Behaviors: A Developing Dyadic Relationship Model

Abstract: The protracted conflict in Iraq and Afghanistan and an all-volunteer military has resulted in multiple war zone deployments for many service members. While quick redeployment turnaround has left little time for readjustment for either the service member or family, dealing with the long-term sequelae of combat exposure often leaves families and intimate partners ill-prepared for years after deployments. Using a modified grounded theory approach, digitally recorded couple interviews of 23 couples were purposeful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 29 publications
1
51
0
2
Order By: Relevance
“…Much of what they discussed reflected aspects of mutuality to include respecting boundaries and mutually agreeing on what and how things would be talked about. We believe these examples helped to differentiate couples that ultimately thrived in their relationships from those who did not (Gerlock et al 2014). …”
Section: Ipv Severity Timeline/monthsmentioning
confidence: 93%
See 2 more Smart Citations
“…Much of what they discussed reflected aspects of mutuality to include respecting boundaries and mutually agreeing on what and how things would be talked about. We believe these examples helped to differentiate couples that ultimately thrived in their relationships from those who did not (Gerlock et al 2014). …”
Section: Ipv Severity Timeline/monthsmentioning
confidence: 93%
“…Many of those in the BIPV-No^group described mutually respectful and supportive behaviors across the span of their relationship, but others reported becoming more so over time. Partners and Veterans also described PTSD and substance abuse treatments as helpful in reducing the overt physical violence, but doing little to reduce the psychological abuse (Gerlock et al 2014). Both as a clinical and research question, would a couple's intervention that incorporated teaching aspects of mutuality for service members and Veterans within the first 2 years' post-deployment help to prevent or reduce the frequency of IPV?…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
See 1 more Smart Citation
“…These changes may be consistent with a diagnosis of posttraumatic stress disorder (PTSD), which often results from exposure to intense and prolonged traumatic circumstances during deployment (Campbell and Renshaw 2013). PTSD often occurs when veterans have experienced intense combat and other traumatic circumstances (Gerlock et al 2013;Monson et al 2009). Rank, (Reger et al 2007), branch, (Castaneda and Harrell 2008) time in the military, and number of deployments, (Blaisure et al 2012) have been found to impact the relationship between PTSD symptoms and reintegration stress.…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 97%
“…Although the majority of research on combat veterans and PTSD addresses the individual trauma response (Gerlock et al 2013), researchers are beginning to investigate the relational aspects of PTSD (Gerlock et al 2013;Monson et al 2009). Specifically, researchers have found strong associations between PTSD symptoms and relationship problems, in that participants who report intense and debilitating PTSD symptoms are also more likely to report greater relationship discord (Monson et al 2009).…”
Section: Ptsd and Family Relationshipsmentioning
confidence: 99%